Analisis SWOT Pemasaran Digital Menggunakan WhatsApp Business Pada Asosiasi Pengusaha Pempek Palembang - Kemas Ahmad Kurniawan; Tata Sutabri (JUSIFO : Jurnal Sistem Informasi, 2023)
This research focuses on analyzing the impact of using whatsapp business in digital marketing on the sales of pempek entrepreneurs' products in Palembang, as well as identifying the effects resulting from the use of whatsapp business. The role of ASPPEK is involved in the study to understand how the use of whatsapp business affects marketing and sales strategies for businesses, especially pempek entrepreneurs in Palembang. Interviews, observations, and literature review were conducted to provide an overview of each factor discussed in the SWOT analysis. This research indicates that the impact of using whatsapp business in digital marketing for the association of pempek entrepreneurs in Palembang has other advantages over marketing strategies, although there are some unavoidable weaknesses due to the use of the application. Increasing the visibility of UMKM products at the association of pempek entrepreneurs in Palembang through product diversification, coupon distribution, and social media promotions. Understanding whatsapp business features allows entrepreneurs to design intelligent digital marketing strategies. Despite the challenges, customer responsiveness and product visibility are strong reasons to adopt this platform.